(3GdJfejI GdRQGYjI GdeSJOGeI GdYhGed GdaYGdI (B/s - (3GdCTQe, eMehOs ((3HjQhJ(B: s (3eQcR OQGSGJ GdhMOI GdYQHjI(B, s, 2007)
(3eaGgje CSGSjI aj GdJfejI GdRQGYjI GdeSJOGeI,OhQ GdefGN aj JMbjb GdJfejI GdRQGYjI GdeSJOGeI,OhQ GdehGQO GdeGFjI aj JMbjb GdJfejI GdRQGYjI GdeSJOGeI,OhQ GdehGQO GdCQVjI hecGaMI GdJUMQ aj JMbjb GdJfejI GdRQGYjI GdeSJOGeI,GdeTcdI GdScGfjI hGdJfejI GdRQGYjI GdeSJOGeI aj GdYGde GdfGej,GdYhGed GdYQHjI GdeSGYOI Ydi JMbjb GdJfejI GdRQGYjI aj GdhWf GdYQHj,GdhVY GdZPGFj GdYGdej hGdYQHj hGdJfejI GdRQGYjI GdeSJOGeIs
(3HHdjhZQGajG(B:(3U U(B.603-621s
Keywords: (3GdJfejI GdRQGYjIs